Teologi Inkulturasi dalam Ritual Selapanan - Kartono (Media (Jurnal Filsafat dan Teologi), 2022)
Selapanan is one of the important rituals in Javanese society. This ritual serves as an expression of gratitude to God for the infant and its mother, as well as asking for safety for the newborn. This paper aims to discuss the theology of inculturation in Selapanan rituals. The author uses the IPA (Interpretative Phenomenological Analysis) method to describe and find the meaning of the Selapanan ritual for Catholic families. The author finds selapanan to be an opportunity to “numumi” (just like the others) and “nguri-uri Kakulturn Jawi” (preserving Javanese culture). This study also intends to offer the possibility that Selapanan ritual would become a locus theologicus for inculturation efforts in the Catholic Church. True inculturation is directed at finding the theological meaning contained behind rituals. In the context of the Selapanan ritual, there are two things to note. First, the salvation of infants does not lie solely in performing rituals, but primarily in faith in Jesus Christ. Second, the prayer for ancestors in Selapanan can be compared to the communio sanctorum in the Catholic tradition.